DAMPAK KENAIKAN HARGA KOMODITAS SEMBAKO TERHADAP TINGKAT INFLASI DI INDONESIA - Darma, Dio Caisar; Pusriadi, Tommy; Hakim, Yundi Permadi (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
The main objectives of the research are: (1) analyzing the effect of price increase of commodity of basic needs on inflation rate in Indonesia; and (2) analyzing variables that have a dominant influence on the level of inflation rate in Indonesia. This research is based on descriptive quantitative and the type of data used is secondary. The data comes from the annual report or publication of several Government Agencies during June 2017-June 2018. The analysis technique uses the Ordinary Least Square (OLS) model and the Statistical Product and Service Solution (SPSS) version 23.0. The test results empirically prove that the variable prices of rice, red onion and red chili commodities have a significant positive effect on the level of inflation rate in Indonesia. Meanwhile, the price of commodities of red chili is a variable that has a dominant influence on the level of inflation rate in Indonesia.